Evaluation of Drug-Drug Interactions in Chronic Kidney Disease Patients: A Single-Center Experience: Drug-drug Interaction in Nephrology Ward - Farnoud, Maryam; Mohammadi, Mojdeh; Mehrpooya, Maryam; Mahboobian, Mohammad Mehdi; Mohammadi, Younes (Iranian Journal of Pharmaceutical Sciences, 2020)
Drug-drug interactions (DDIs) result from the simultaneous consumption of two or more drugs that alter the patient’s response to the initial drug. The treatment regimen in patients with kidney disease is very diverse and may be associated with several diseases that increases the risk of DDIs. This study was carried out to investigate the DDIs incidence in patients with chronic kidney disease (CKD) in the nephrology ward. This descriptiveanalytical study was performed in a 4-month period in 2017. The patients’ information, such as age, sex, list of drugs during hospitalization, and kidney disease stage were recorded from patients’ medical records. Drug-drug interactions were extracted using LexiComp Online. In this study 48.55% of patients were male, 51.45% were female, and 53.2% of patients were in stage 5 of kidney disease. There was a significant correlation between the incidence of drug-drug interactions with stage 5 of disease (P=0.02). The highest number of interactions was categorized as type C and interaction between atorvastatin and pantoprazole was the most frequent interaction. The maximum range of prescription drugs was between 6 and 10 items by 49.7% of patients. There was a significant correlation between the incidence of drug-drug interactions and the number of prescribed drugs (P=0.03). Drug-drug interactions are common in patients with chronic kidney disease. Based on the results, the number of prescribed drugs and the stage of the disease are effective in drug-drug interactions incidence. It is possible to reduce drug complications and to increase the life span of patients by recognizing drug-drug interactions.